Correlation of Salt Intake and Physical Activity with Hypertension among University Students - Muthmainah Muthmainah; Salsabila Nur Azizah Harinda Putri; Adi Magna Patriadi Nuhriawangsa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a major health problem in Indonesia, the city of Surakarta reporting a prevalence of 78.65% among non communicable diseases in 2023. Cases are also found in university students. They are vulnerable to unhealthy lifestyle changes, such as high salt (sodium) intake and low activity levels. This study aimed to determine the relationship between the salt intake and physical activity with hypertension among university students in Surakarta. A cross-sectional study involved 106 students selected by purposive sampling. Blood pressure was measured with a digital sphygmomanometer, salt intake were assessed with the SQFFQ, and physical activity was measured with the IPAQ. Data were analyzed using Spearman Rank and Binary Logistic Regression tests. The results showed that there was a significant association between salt intake and physical activity with hypertension (p = 0.001). The Negelkerke R Square result showed 0.287, indicating that students with high salt intake and low activity levels had an increased risk of hypertension. In conclusion, high salt intake and low physical activity significantly contribute to 28.7% of hypertension cases. Students are advised to reduced salt consumption and regular physical activity to promote a healthier lifestyle.